ANALYSIS OF AN RGBD CAMERA FOR MANHOLE INSPECTION - Jorge, Filipe Castanheira (2020)
As the service life of ducts and manholes reaches their end, there is a growing need to preserve the structures. In order to prevent casualties and service interruption, more frequent inspections are advised. To this day most of the inspections are still, manually made. These inspectors need to be highly qualified, and the inspections are done in an hazardous environment so, automating the inspection process would lead to a healthier workplace. Given the recent development in RGBD cameras, with smaller size factor, cost, and weight, this project aims to evaluate the application of one of the more recent models in a manhole inspection environment. Several analysis are done to assess the RGBD sensor performance for 3D model reconstruction, including the comparison with a ground-truth 3D model obtained using a laser point profile sensor with an industrial robot.